Aliskiren in early postnatal life prevents hypertension and reduces asymmetric dimethylarginine in offspring exposed to maternal caloric restriction. (September 2015) - Hsu, Chien-Ning; Lee, Chien-Te; Huang, Li-Tung; Tain, You-Lin
Introduction: Asymmetric dimethylarginine (ADMA), an endogenous inhibitor of nitric oxide synthase, is involved in hypertension. We tested whether aliskiren treatment in early postnatal life can reduce ADMA and regulate the renin-angiotensin system to prevent hypertension in rat offspring exposed to maternal caloric restriction (CR). Materials and methods: Four groups of 12-week-old male offspring were sacrificed: control, CR, CR+aliskiren, and CR+losartan group. The CR group included offspring from 50% food-restricted maternal rats. The CR+aliskiren and CR+losartan groups were produced by treating CR offspring with oral aliskiren 10 mg/kg/day or losartan 20 mg/kg/day between 2–4 weeks of age, respectively. Results: Blood pressure increased in CR rats, which was prevented by aliskiren or losartan. CR increased plasma ADMA levels, which aliskiren prevented. Renal renin and prorenin receptor (PRR) expression increased in CR rats treated with aliskiren, whereas both were reduced by losartan. Both aliskiren and losartan decreased renal mRNA expression of angiotensinogen, angiotensin II type 2 receptor, and Mas in CR rats. However, aliskiren increased angiotensin II type 2 receptor and Mas protein levels in CR kidneys. Conclusions: Early aliskiren therapy prevents CR-induced hypertension via ADMA reduction, decreases angiotensinogen expression, and increases renal angiotensin II type 2 receptor and Mas protein.